2011
DOI: 10.15288/jsad.2011.72.669
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of Alcohol Pharmacotherapy Adoption in Substance Use Disorder Treatment Programs: Patterns of Sustainability and Discontinuation

Abstract: ABSTRACT. Objective: The objectives of this study were to (a) identify the patterns of disulfi ram (Antabuse) and tablet naltrexone (Revia) adoption over a 48-month period in a nationally representative sample of privately funded programs that deliver substance use disorder treatment; (b) examine predictors of sustainability, later adoption, discontinuation, and nonadoption of disulfi ram and tablet naltrexone; and (c) measure reasons for medication discontinuation. Method: Two waves of data were collected via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…A study examining the early adoption of injectable naltrexone for AUD found that the percentage of patients with private insurance was positively associated with adoption (Abraham & Roman, 2010). Patient payer source and revenues from private insurance have been linked to greater adoption of other medications for AUD as well (Abraham et al, 2011;Ducharme et al, 2006;Fuller et al, 2005;Thomas et al, 2003). Although public payer sources often cover the use of SUD medications (Lichtenberg and Philipson, 2002), injectable naltrexone is usually covered as a Medicaid medical benefi t rather than a pharmacy benefi t (American Society of Addiction Medicine [ASAM], 2013), unlike other medications, which are almost always covered under pharmacy benefi ts.…”
Section: Facilitators To the Adoption Of Injectable Naltrexonementioning
confidence: 99%
See 2 more Smart Citations
“…A study examining the early adoption of injectable naltrexone for AUD found that the percentage of patients with private insurance was positively associated with adoption (Abraham & Roman, 2010). Patient payer source and revenues from private insurance have been linked to greater adoption of other medications for AUD as well (Abraham et al, 2011;Ducharme et al, 2006;Fuller et al, 2005;Thomas et al, 2003). Although public payer sources often cover the use of SUD medications (Lichtenberg and Philipson, 2002), injectable naltrexone is usually covered as a Medicaid medical benefi t rather than a pharmacy benefi t (American Society of Addiction Medicine [ASAM], 2013), unlike other medications, which are almost always covered under pharmacy benefi ts.…”
Section: Facilitators To the Adoption Of Injectable Naltrexonementioning
confidence: 99%
“…Other studies using samples of prisons, jails, or community corrections agencies indicate that MAT is rarely used (Friedmann et al, 2012;Matusow et al, 2013;Taxman et al, 2007). As a result, a treatment center's connection with the criminal justice system has been shown to be associated with both less adoption and less sustained use of medications for AUD and opioid use disorder (Abraham et al, 2011;Ducharme et al, 2006;Knudsen & Roman, 2012).…”
Section: Barriers To the Adoption Of Injectable Naltrexonementioning
confidence: 99%
See 1 more Smart Citation
“…Turning back to the use of SUD medication, most previous studies of medication adoption have considered single medications rather than the breadth of pharmacotherapy services Abraham et al, , 2011Fuller et al, 2005;Knudsen et al, 2005;Koch et al, 2006;Roman, 2007, 2008;Roman and Johnson, 2002;Thomas et al, 2003Thomas et al, , 2008. For the present research question, gauging the relationship of physician presence to organizational availability of pharmacotherapies, the number of available SUD medications is the appropriate variable to consider, and this focus is a novel contribution to the literature.…”
mentioning
confidence: 97%
“…The American Society of Addiction Medicine (ASAM) Performance Measures for the Addiction Specialist Physician also include a suggested measure related to receipt of AUD pharmacotherapy (American Society of Addiction Medicine 2014). Changes in prescribing rates could be determined after initiatives to educate clinicians or reduce barriers to pharmacotherapy use (Abraham et al 2011;Harris et al 2016). Electronic decision support could identify individuals with a new diagnosis of moderate to severe AUD (as documented as a problem or diagnosis) and provide information on acamprosate and naltrexone for consideration by the clinician through a passive alert or "infobutton" (Del Fiol et al 2012 …”
Section: Quality Measurement Considerationsmentioning
confidence: 99%